The contribution of online news consumption to critical-reflective journalism professionals: likelihood patterns among greek journalism students - Veglis, Andreas A.; Spyridou, Lia Paschalia (My University, 2008)
Evidence suggests that the internet is the medium with the most success in attracting young people to news, while traditional media have been facing increasing trouble since the 1980s. The emergence of cynical and sceptical attitudes about politics and the media has resulted in most young people becoming 'news grazers' instead of regular news consumers. Journalism students, however, should be exposed to political information not only as part of their civic obligation, but also in order to be fully equipped to make essential contributions as future analysts and brokers of news. By proposing a conceptual approach on how online news consumption contributes to critical reflective journalism, and drawing upon informed citizenry theory, the knowledge gap hypothesis, the diffusion of innovations model and the uses and gratification perspective, this article attempts to investigate the determinants and consumption patterns of online news by journalists-to-be in Greece. It is argued that conventional predictors such as possession of substantial cultural capital and longer surfing hours have supremacy over the perceived utility of self-education, job experience and simulation
Keywords: Journalism, Educational; Political culture; Journalism